A review of the evidence on reducing macrovascular risk in patients with atherogenic dyslipidaemia: A report from an expert consensus meeting on the role of fenofibrate-statin combination therapy - Aguiar, Carlos; Alegria, Eduardo; Bonadonna, Riccardo C; Catapano, Alberico L; Cosentino, Francesco; Elisaf, Moses; Farnier, Michel; Ferrières, Jean; Filardi, Pasquale Perrone; Hancu, Nicolae; Kayikcioglu, Meral; Mello E Silva, Alberto; et al. (Atherosclerosis. Supplements, 2015)
A meeting of European experts in cardiovascular (CV) disease and lipids was convened in Paris, France, on 10 November 2014 to discuss lipid profile, and in particular atherogenic dyslipidaemia (AD), and associated CV risk. Key points that were raised and discussed during the meeting are summarised in this paper, which also accounts for further discussion and agreement on these points by the group of experts. Elevated levels of low-density lipoprotein cholesterol (LDL-c) are commonly associated with a greater CV risk than low LDL-c levels, and are routinely managed with statins. However, even for patients controlled on statins and achieving low LDL-c levels, abnormal lipid profiles observed in some patients (i.e. elevated triglyceride levels, with/without low levels of high-density lipoprotein cholesterol [HDL-c]) have been linked to the presence of a residual CV risk. Therefore, it is recommended that both triglyceride and HDL-c levels be measured, to allow for the overall CV residual risk to be adequately managed. Favourable safety and clinical data support the combination of statins with other lipid-lowering agents, such as fenofibrate. Patients who have elevated triglyceride levels plus low levels of HDL-c are most likely to achieve clinical benefit from fenofibrate-statin combination therapy. In these patients with AD, achieving target non-HDL-c levels should be a key focus of CV risk management, and the use of non-HDL-c was advocated to provide a better measure of CV risk than LDL-c levels.
Keywords: combination therapy; fenofibrate; Paříž; lipidy; statins; Europe; fenofibrát; Drug Therapy, Combination; Evropa; Diabetes Mellitus, Type 2; cardiovascular risk; ateroskleróza; diabetes mellitus 2. typu; Atherosclerosis; Paris; Fenofibrate; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Lipids; Cardiovascular Diseases; kombinovaná farmakoterapie; dyslipidemie; Humans; statiny; hypolipidemika; Hypolipidemic Agents; Atherogenic dyslipidaemia; triglycerides; Dyslipidemias; kardiovaskulární nemoci; lidé; cholesterol